Pengaruh Pengalaman Dan Kepatuhan Kode Etik Terhadap Pencegahan Kecurangan Pada Inspektorat Kota Padang - Rahmaita .; Margaretta Hilda Laia (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of auditor experience and compliance with the code of ethics on fraud prevention at the Padang City Inspectorate. A quantitative approach with a survey method was employed. The population consisted of 64 Government Internal Supervisory Apparatus (APIP) at the Padang City Inspectorate, all of whom were included as samples using a saturated sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method. The results indicate that auditor experience has a positive effect on fraud prevention, with a path coefficient of 0.630. Similarly, compliance with the code of ethics also shows a positive effect, with a path coefficient of 0.227. These findings suggest that higher auditor experience and better adherence to the code of ethics lead to more effective fraud prevention efforts within the Padang City Inspectorate.